Supermolecule-nanocellulose composite diaphragm as well as preparation method and application thereof

By forming a supramolecular-nanocellulose composite separator with a supramolecular-based polyester layer on the surface of the nanocellulose membrane, the defects of glass fiber separators in aqueous zinc-ion batteries are solved, achieving long life and high safety of zinc-ion batteries.

CN121035528APending Publication Date: 2025-11-28TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511168073.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing aqueous zinc-ion batteries use glass fiber separators, resulting in poor battery cycle performance, inability to suppress zinc dendrite growth and puncture, easy hydrogen evolution corrosion, and lack of ion transport selectivity and uniform deposition capability.

Method used

A supramolecular-nanocellulose composite membrane is used. A supramolecular polyester layer is formed on the surface of the nanocellulose membrane by interfacial polymerization. By combining supramolecular and nanocellulose, a continuous and defect-free cross-linked network is formed, which regulates the diffusion path of zinc ions and inhibits dendrite growth and side reactions.

Benefits of technology

It improves the cycle life and safety of zinc-ion batteries, ensures uniform ion deposition, enhances mechanical integrity and electrolyte retention capacity, and achieves long-life, high-safety aqueous zinc-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035528A_ABST
    Figure CN121035528A_ABST
Patent Text Reader

Abstract

The invention provides a supramolecular-nanocellulose composite diaphragm as well as a preparation method and application thereof, and relates to the field of new energy. The supramolecular-nanocellulose composite diaphragm is composed of a nanocellulose membrane and a supramolecular-based polyester layer on the surface of the single side of the nanocellulose membrane, and the supramolecular-based polyester layer is formed on the surface of the single side of the nanocellulose membrane through an interfacial polymerization method by taking the nanocellulose membrane as a supporting body, supramolecular as a reaction monomer and 1, 3, 5-benzoyl chloride as a cross-linking agent. The supramolecular-nanocellulose composite diaphragm subjected to unilateral interfacial polymerization has a special microporous structure consisting of supramolecules and nanocellulose, so that a desolvation process is facilitated; and meanwhile, the supermolecule can effectively regulate and control the diffusion path of zinc ions by virtue of a unique cavity structure and a steric hindrance effect and reduce local charge aggregation, so that dendritic crystal growth is inhibited, electric field distribution is more uniform, a desolvation process is enhanced, and the effects of inhibiting side reaction and realizing uniform deposition or dissolution of ions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of new energy, in particular to a supramolecular-nanocellulose composite diaphragm and a preparation method and application thereof. BACKGROUND

[0002] Using renewable energy such as wind energy, solar energy and tidal energy to replace non-renewable energy such as oil and coal is one of the effective ways to balance the relationship between industrial development and environmental protection. However, unlike traditional fossil energy, new energy such as solar energy, tidal energy and wind energy has the disadvantages of intermittency, non-sustainability and instability. Therefore, developing efficient and reliable energy storage technology to store unstable energy and release it at peak electricity consumption is an effective strategy for using intermittent new energy.

[0003] With the development and innovation of lithium ion battery technology, such batteries have a broad application prospect in the fields of smart phones, wearable electronic devices and electric vehicles due to their high energy density and super-long cycle life. However, the current key raw materials for lithium ion batteries are scarce, the cost is high, and the safety performance is poor, which limits their application in remote areas and large-scale energy storage. Aqueous rechargeable batteries not only avoid the flammable problem of organic electrolyte, but also have high ionic conductivity, which is conducive to the rapid transfer of ions. Aqueous zinc ion batteries have attracted the attention of researchers due to the high abundance, low redox potential, high environmental humidity tolerance, high hydrogen evolution overpotential and high volume energy density of metal zinc. Aqueous rechargeable zinc ion batteries are extremely competitive candidates in the field of large-scale energy storage due to their high safety, low cost and simple production environment.

[0004] Most of the research on aqueous zinc ion batteries uses glass fiber diaphragms, because the main component of glass fiber is silicon dioxide, which has higher stability in aqueous environment; at the same time, the loose structure is beneficial to improve the porosity of glass fiber and reduce the resistance of ion transfer in electrolyte. However, glass fiber diaphragms have some problems that hinder their large-scale application: 1) unable to inhibit or prevent the growth and penetration of zinc dendrites; 2) prone to hydrogen evolution, corrosion and other side reactions; 3) lack of selectivity and guidance ability for ion transfer, and unable to promote uniform deposition. The above problems ultimately lead to the defect of poor cycle performance of aqueous zinc ion batteries. Therefore, how to overcome the above defects of glass fiber diaphragm and provide a diaphragm material more suitable for aqueous zinc ion batteries is a problem to be solved by those skilled in the art. SUMMARY

[0005] Therefore, the technical problem to be solved by the present application is to overcome the defect of poor cycle performance of aqueous zinc ion batteries caused by the use of glass fiber diaphragm in the prior art, so as to provide a supramolecular-nanocellulose composite diaphragm and a preparation method and application thereof.

[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a supramolecular-nanocellulose composite membrane, which is composed of a nanocellulose membrane and a supramolecular-based polyester layer on one side surface. The supramolecular-based polyester layer is formed on one side surface of the nanocellulose membrane by interfacial polymerization using a nanocellulose membrane as a support, supramolecular monomers as reactants, and 1,3,5-benzenetricarboxyl chloride as a crosslinking agent.

[0007] Furthermore, the supramolecular element is selected from at least one of cyclodextrin, calixarene, columnar aromatics, and crown ethers. β-cyclodextrin is preferred.

[0008] Secondly, the present invention provides a method for preparing the supramolecular-nanocellulose composite membrane, comprising the following steps: fully impregnating the nanocellulose membrane with a supramolecular solution, removing it and then adding a 1,3,5-benzenetricarboxyl chloride solution to one side surface of the nanocellulose membrane to induce an interfacial polymerization reaction, removing it after the reaction is completed to obtain the supramolecular-nanocellulose composite membrane.

[0009] Furthermore, the preparation method of the nanocellulose membrane includes: dissolving cellulose nanofibers in deionized water, stirring thoroughly, and filtering using a vacuum filtration method to obtain the nanocellulose membrane. The thickness of the nanocellulose membrane is approximately 0.65~0.75 mm.

[0010] Furthermore, the ratio of the cellulose nanofibers to deionized water is 0.045~0.06 g:100 mL, preferably 0.06 g:100 mL.

[0011] The stirring conditions are: rotation speed 500~700 r / min, preferably 600 r / min; stirring time 0.5~2 h, preferably 1 h; Furthermore, the vacuum filtration conditions are as follows: using a filter membrane with a pore size of 40~50 μm and a diameter of 45~60 mm, filtration is carried out for 30~50 min at a temperature of 22~27 ℃ and a vacuum degree of 0.07~0.09 MPa. Preferably, a filter membrane with a pore size of 45 μm and a diameter of 50 mm is used, and filtration is carried out for 40 min at a temperature of 25 ℃ and a vacuum degree of 0.08 MPa.

[0012] Further, the solvent of the supramolecular solution is deionized water; the concentration of the supramolecular solution is 0.001~0.1 mol / L, preferably 0.01~0.02 mol / L; the pH value of the supramolecular solution is 10~13; the ratio of the supramolecular solution to the nanocellulose membrane is 6~8 mL: 0.045~0.06 g, preferably 8 mL: 0.06 g.

[0013] Further, the solvent of the 1,3,5-benzenetriformyl chloride solution is n-heptane; the mass ratio of the 1,3,5-benzenetriformyl chloride solution to the solvent in the 1,3,5-benzenetriformyl chloride solution is 1:10~100, preferably 1:40~60, more preferably 1:50; the ratio of the 1,3,5-benzenetriformyl chloride solution to the nanocellulose membrane is 5~6 mL:0.045~0.06 g, preferably 6 mL:0.06 g.

[0014] Further, the conditions for the interfacial polymerization reaction are as follows: first react at 23~25 °C for 5~40 min, remove excess solution from the membrane surface, and then react at 50~60 °C for 5~40 min. Preferably, react at 23~25 °C for 5~20 min, remove excess solution from the membrane surface, and then react at 50~60 °C for 5~20 min; more preferably, react at 25 °C for 20 min, remove excess solution from the membrane surface, and then react at 60 °C for 20 min.

[0015] Thirdly, the present invention provides the application of the supramolecular-nanocellulose composite membrane or the supramolecular-nanocellulose composite membrane obtained by the preparation method in the preparation of aqueous zinc-ion batteries.

[0016] Fourthly, the present invention provides an aqueous zinc-ion battery, comprising the supramolecular-nanocellulose composite separator or the supramolecular-nanocellulose composite separator obtained by the preparation method.

[0017] Furthermore, the aqueous zinc-ion battery is of the type of zinc-zinc symmetric battery or zinc-vanadium pentoxide full battery.

[0018] Furthermore, the separator of the aqueous zinc-ion battery is composed of a glass fiber separator and supramolecular-nanocellulose composite separators disposed on both sides thereof, wherein the supramolecular-based polyester layer side of the supramolecular-nanocellulose composite separator faces away from the glass fiber separator.

[0019] Furthermore, the zinc-zinc symmetric battery includes, in sequence, a negative electrode shell, a spring, a gasket, a zinc negative electrode, a supramolecular-nanocellulose composite membrane, a glass fiber membrane, a supramolecular-nanocellulose composite membrane, a zinc positive electrode, a positive electrode shell, and an electrolyte filled between the zinc negative electrode and the zinc positive electrode, wherein the supramolecular-nanocellulose composite membrane has a supramolecular-based polyester layer located on the side opposite to the glass fiber membrane; Furthermore, the zinc-vanadium pentoxide full cell includes, in sequence, a negative electrode shell, a spring, a gasket, a zinc negative electrode, a supramolecular-nanocellulose composite membrane, a glass fiber membrane, a supramolecular-nanocellulose composite membrane, a vanadium pentoxide positive electrode, a positive electrode shell, and an electrolyte filled between the zinc negative electrode and the vanadium pentoxide positive electrode, wherein the supramolecular-based polyester layer of the supramolecular-nanocellulose composite membrane is located on the side opposite to the glass fiber membrane.

[0020] The technical solution provided by this invention has the following advantages: The supramolecular-nanocellulose composite membrane provided by this invention uses a nanocellulose membrane as a support, providing a stable substrate for the supramolecular molecules. Its hydrophilic pores facilitate the permeation of the supramolecular solution, allowing the supramolecular molecules to diffuse uniformly into the nanocellulose membrane. During interfacial polymerization, the supramolecular molecules and 1,3,5-benzenetricarboxyl chloride undergo an esterification reaction on the surface of the nanocellulose membrane. The presence of the nanocellulose membrane promotes a uniform crosslinking reaction between the supramolecular molecules and 1,3,5-benzenetricarboxyl chloride, forming a continuous and defect-free crosslinking network. Once the crosslinking layer is formed, it prevents more supramolecular molecules from diffusing from the pores of the nanocellulose membrane to the reaction interface, thus naturally terminating the crosslinking reaction. Ultimately, a high-quality supramolecular-based polyester crosslinking layer is formed on the surface of the nanocellulose membrane, making the membrane surface smoother and more uniform, and preventing structural damage or performance degradation of the membrane during use.

[0021] The supramolecular-nanocellulose composite membrane is produced by cross-linking the nanocellulose membrane substrate directly through interfacial polymerization. This method has the advantages of high efficiency, environmental friendliness, and low cost.

[0022] The supramolecular-nanocellulose composite membrane, which has undergone unilateral interfacial polymerization, has a special microporous structure composed of supramolecular and nanocellulose, which is conducive to the desolvation process. At the same time, the supramolecular structure can effectively regulate the diffusion path of zinc ions by means of its unique cavity structure and steric hindrance effect, reduce local charge accumulation, thereby inhibiting dendrite growth, making the electric field distribution more uniform, which helps to enhance the desolvation process, and achieve the effects of suppressing side reactions and realizing uniform ion deposition or dissolution.

[0023] The supramolecular-nanocellulose composite separator provided by this invention can be used in aqueous zinc-ion batteries. It is an important component of zinc-ion rechargeable batteries. Its basic function is to separate the positive and negative electrodes, store the electrolyte, and allow the anions and cations to pass through, so as to ensure the balanced state between the positive and negative electrodes.

[0024] The separator for an aqueous zinc-ion battery provided by this invention consists of a glass fiber separator and supramolecular-nanocellulose composite separators disposed on both sides thereon, wherein the supramolecular-based polyester layer side of the supramolecular-nanocellulose composite separator faces away from the glass fiber separator. By directly placing the supramolecular functional layer on the interface facing the electrode (especially the zinc anode), it can maximize its core role in regulating ion flow, suppressing dendrites, and minimizing side reactions. Utilizing the strong support and high porosity of glass fiber, the excellent hydrophilicity and binding properties of nanocellulose, and the interfacial functionalization capabilities of supramolecular materials, synergistic optimization is achieved, solving the problems of zinc dendrites and interfacial side reactions in aqueous zinc-ion batteries, while ensuring good ion transport, mechanical integrity, and electrolyte retention capacity. This provides a separator solution for constructing long-life, high-safety aqueous zinc-ion batteries.

[0025] The application of supramolecular-nanocellulose composite membranes in aqueous zinc-ion batteries results in a more uniform and dense zinc anode surface with a simpler morphology, exhibiting uniform and dense zinc ion deposition behavior, which is beneficial for long-term cycling. Zinc-zinc symmetric batteries assembled using supramolecular-nanocellulose composite membranes demonstrate ultra-long cycle life, far exceeding that of batteries using glass fiber membranes directly. Furthermore, the symmetric batteries maintain a relatively stable voltage distribution under high current conditions and retain a certain degree of electrochemical reversibility even at high current densities. Zinc-vanadium pentoxide full cells assembled using supramolecular-nanocellulose composite membranes all exhibit good capacity retention (>80%). Attached Figure Description

[0026] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0027] Figure 1 This is a scanning electron microscope image of the supramolecular-nanocellulose composite membrane prepared in Example 1 of this invention; Figure 2 This is a scanning electron microscope image of the nanocellulose membrane prepared in Comparative Example 1 of this invention; Figure 3This is a scanning electron microscope image of the zinc anode surface after 60 h of cycling of the zinc-zinc (Zn-Zn) symmetric battery assembled in Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the zinc anode surface after 60 h of cycling of the zinc-zinc (Zn-Zn) symmetric battery assembled in Comparative Example 3 of the present invention. Figure 5 This is a scanning electron microscope image of the zinc negative electrode after ion beam sputtering following 60 h of cycling of the zinc-zinc (Zn-Zn) symmetric battery assembled in Example 1 of the present invention. Figure 6 This is a scanning electron microscope image of the zinc negative electrode after ion beam sputtering following 60 h of cycling of the zinc-zinc (Zn-Zn) symmetric battery assembled in Comparative Example 3 of this invention. Figure 7 This is a cycle performance diagram of the zinc-zinc (Zn-Zn) symmetric batteries assembled in Embodiments 1, 4, 5, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention; Figure 8 These are critical current density test graphs of the zinc-zinc (Zn-Zn) symmetric cells assembled in Embodiments 1, 2, 3 and Comparative Example 3 of the present invention; Figure 9 This is a cycle performance analysis diagram of the zinc-vanadium pentoxide (Zn-V2O5) full cells assembled in Examples 1, 4, 5, Comparative Examples 1, 2, and 3 of this invention. Detailed Implementation

[0028] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0029] The sources of raw materials are shown in Table 1.

[0030] Table 1. Sources of raw materials

[0031] The sources of the instruments are shown in Table 2.

[0032] Table 2. Instrument Sources

[0033] Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. All raw materials or instruments used are commercially available conventional products, including but not limited to those used in the embodiments of this application.

[0034] Example 1 This embodiment provides a cyclodextrin-nanocellulose composite membrane (10), which is composed of a nanocellulose membrane and a supramolecular polyester layer on one side surface. The supramolecular polyester layer is formed on one side surface of the nanocellulose membrane by interfacial polymerization using the nanocellulose membrane as a support, β-cyclodextrin as a reactive monomer, and 1,3,5-benzenetricarboxyl chloride as a crosslinking agent.

[0035] The specific preparation steps of the cyclodextrin-nanocellulose composite membrane (10) are as follows: (1) Preparation of nanocellulose membrane: 60 mg of cellulose nanofibers were dissolved in 100 mL of deionized water and stirred thoroughly (600 r / min, 1 h) to disperse them evenly. Vacuum filtration was carried out using a filter membrane with a pore size of 45 μm and a diameter of 50 mm at a temperature of 25 ℃ and a vacuum degree of 0.08 MPa for 40 min to obtain a nanocellulose membrane with a thickness of 0.69 mm. (2) Solution preparation: β-cyclodextrin was dissolved in deionized water to prepare a supramolecular solution with a concentration of 0.0175 mol / L and a pH of 13; 1,3,5-benzenetricarboxyl chloride was dissolved in n-heptane (1,3,5-benzenetricarboxyl chloride: n-heptane = 1:50, w / w) to prepare a 1,3,5-benzenetricarboxyl chloride solution; (3) Preparation of composite membrane: 0.06 g of nanocellulose membrane was fully impregnated with 8 mL of supramolecular solution. After taking it out, 6 mL of 1,3,5-benzenetricarboxyl chloride solution was dropped onto one side of the nanocellulose membrane. The reaction was first carried out at room temperature (25 °C) for 20 min, and the excess solution on the membrane surface was removed. Then the reaction was carried out at 60 °C for 20 min. After the interfacial polymerization reaction was completed, the membrane was taken out to obtain cyclodextrin-nanocellulose composite membrane (10).

[0036] This embodiment also provides a zinc-zinc (Zn-Zn) symmetrical battery, the structure of which and its assembly process are as follows: The prepared cyclodextrin-nanocellulose composite separator (10) was cut into a circle with a diameter of 16 mm and assembled into a zinc-zinc (Zn-Zn) symmetrical battery using a button battery casing. The symmetrical battery assembly process was as follows: the negative electrode shell, spring, gasket, zinc negative electrode (circular zinc foil with a diameter of 12 mm), battery separator (composite separator-glass fiber separator-composite separator, with the supramolecular polyester layer of the composite separator facing away from the glass fiber separator), electrolyte (3 mol / L zinc trifluoromethanesulfonate solution, 150 μL), zinc positive electrode (circular zinc foil with a diameter of 12 mm), and positive electrode shell were assembled in sequence. After assembly, the battery was sealed using a battery sealing machine.

[0037] This embodiment also provides a zinc-vanadium pentoxide (Zn-V2O5) full battery, the structure and assembly process of which are as follows: the prepared cyclodextrin-nanocellulose composite membrane (10) is cut into a circle with a diameter of 16 mm, and assembled into a zinc-vanadium pentoxide (Zn-V2O5) full battery using a button battery shell. The full battery assembly process is as follows: negative electrode shell, spring sheet, gasket, zinc negative electrode (12mm diameter circular zinc foil), battery separator (composite separator—glass fiber separator—composite separator, with the supramolecular polyester layer of the composite separator facing away from the glass fiber separator), electrolyte (3 mol / L zinc trifluoromethanesulfonate solution, 150 μL), vanadium pentoxide positive electrode (vanadium pentoxide powder treated by hydrothermal method, conductive carbon black, and polyvinylidene fluoride powder are mixed at a mass ratio of 7:2:1 and thoroughly ground; the resulting powder is mixed with N-methylpyrrolidone solvent at a ratio of 20 mg / mL and ultrasonically treated for 1 h; the resulting slurry is drop-coated onto a 12 mm diameter carbon cloth substrate and dried at 80 ℃ for 12 h, yielding a vanadium pentoxide loading of 0.68 mg / cm³). 2 The vanadium pentoxide positive electrode sheet and the positive electrode shell are assembled in sequence. After assembly, the battery is sealed using a battery sealing machine.

[0038] Example 2 This embodiment provides a cyclodextrin-nanocellulose composite membrane (11), the preparation steps of which are the same as those in Example 1. The only difference is that in step (3), the interfacial polymerization reaction conditions are: first react at room temperature (25 °C) for 20 min to remove excess solution from the membrane surface, and then react at 60 °C for 5 min.

[0039] This embodiment also provides a zinc-zinc (Zn-Zn) symmetric battery and a zinc-vanadium pentoxide (Zn-V2O5) full battery based on the cyclodextrin-nanocellulose composite membrane (11), the structure and assembly process of which are the same as in Example 1.

[0040] Example 3 This embodiment provides a cyclodextrin-nanocellulose composite membrane (12), the preparation steps of which are the same as those in Example 1. The only difference is that in step (3), the interfacial polymerization reaction conditions are: first react at room temperature (25 °C) for 20 min to remove excess solution from the membrane surface, and then react at 60 °C for 10 min.

[0041] This embodiment also provides a zinc-zinc (Zn-Zn) symmetric battery and a zinc-vanadium pentoxide (Zn-V2O5) full battery based on the cyclodextrin-nanocellulose composite membrane (12), the structure and assembly process of which are the same as in Example 1.

[0042] Example 4 This embodiment provides a calixarene-nanocellulose composite membrane (20), the preparation steps of which are the same as in Example 1, except that β-cyclodextrin is replaced with calixarene[4].

[0043] This embodiment also provides a zinc-zinc (Zn-Zn) symmetric battery and a zinc-vanadium pentoxide (Zn-V2O5) full battery based on the calixarene-nanocellulose composite membrane (20), the structure and assembly process of which are the same as in Example 1.

[0044] Example 5 This embodiment provides a columnar aromatic hydrocarbon-nanocellulose composite membrane (30), the preparation steps of which are the same as in Example 1, except that β-cyclodextrin is replaced with columnar aromatic hydrocarbon.

[0045] This embodiment also provides a zinc-zinc (Zn-Zn) symmetric battery and a zinc-vanadium pentoxide (Zn-V2O5) full battery based on the aromatic hydrocarbon-nanocellulose composite membrane (30), the structure and assembly process of which are the same as in Example 1.

[0046] Comparative Example 1 This comparative example provides an acyl chloride nanocellulose membrane (40), the specific preparation steps of which are as follows: Take the nanocellulose membrane prepared according to Example 1 and the 1,3,5-benzenetricarboxyl chloride solution respectively, and add 6 mL of 1,3,5-benzenetricarboxyl chloride solution to one side of the surface of the 0.06 g nanocellulose membrane. Place it at 60 ℃ for 20 min to obtain the acyl chloride nanocellulose membrane (40).

[0047] This comparative example also provides zinc-zinc (Zn-Zn) symmetric cells and zinc-vanadium pentoxide (Zn-V2O5) full cells based on the acyl chloride nanocellulose membrane (40), the structure and assembly process of which are the same as in Example 1.

[0048] Comparative Example 2 This comparative example provides a nanocellulose membrane (50), the specific preparation of which is described in step (1) of Example 1.

[0049] This comparative example also provides zinc-zinc (Zn-Zn) symmetric cells and zinc-vanadium pentoxide (Zn-V2O5) full cells based on the nanocellulose membrane (50), the structure and assembly process of which are the same as in Example 1.

[0050] Comparative Example 3 This comparative example provides a commercially available glass fiber diaphragm (60).

[0051] This comparative example also provides zinc-zinc (Zn-Zn) symmetric cells and zinc-vanadium pentoxide (Zn-V2O5) full cells based on the glass fiber membrane (60), the structure and assembly process of which are the same as in Example 1.

[0052] Microstructure observation of composite membrane in Experiment Example 1 The cyclodextrin-cellulose nanocomposite membrane (10) prepared in Example 1 and the acyl chloride cellulose nanocomposite membrane (40) prepared in Comparative Example 1 were observed using a scanning electron microscope (SEM). The SEM images were magnified to 1000x and are shown below. Figure 1 and Figure 2 As shown, the surface of the cyclodextrin-nanocellulose composite membrane (10) is smoother than that of the acyl chloride nanocellulose membrane (40). This is because in the cyclodextrin-nanocellulose composite membrane (10), the surface of the nanocellulose membrane is covered by a supramolecular polyester layer formed by interfacial polymerization. The microporous structure of the membrane is composed of supramolecular and nanocellulose. This special microporous structure and the special cavity structure of the supramolecular can effectively improve the desolvation process. The composite membrane can better regulate the zinc ion concentration in the environment and make the electric field distribution more uniform.

[0053] Experiment Example 2: Cyclic Stability Test of Zinc-Zinc Symmetric Cells 1. Experimental Procedure The zinc-zinc symmetric batteries assembled in Example 1 and Comparative Example 3 were tested at 25°C and 1 mAh cm⁻¹. -2 After cycling for 60 hours under the specified conditions, the zinc negative electrode of the battery was taken, and its microstructure at 2500x magnification was observed using a scanning electron microscope. The scanning electron microscope images are shown below. Figure 3 and Figure 4 As shown in the figure. After the zinc anode was subjected to ion beam sputtering (current 100 nA, sputtering depth > 5 μm), the microstructure of its surface was observed using a scanning electron microscope. The scanning electron microscope images are shown in the figure. Figure 5 and Figure 6 As shown.

[0054] The zinc-zinc symmetric batteries assembled in Examples 1, 4, 5, Comparative Examples 1, 2, and 3 were tested at 25°C and 0.5 mAh cm⁻¹. -2 Its cycling performance was tested under the conditions, and the results are as follows: Figure 7 As shown.

[0055] The testing equipment used for the cycle stability test was the Xinwei Battery Testing System.

[0056] 2. Results Analysis like Figure 7 As shown, the symmetric battery assembled using a cyclodextrin-nanocellulose composite membrane (10) remained stable after 3500 h of cycling.Figure 3 and Figure 5 As shown, after 60 h of cycling, the surface of the zinc anode is more uniform and dense with a single morphology in the symmetrical battery assembled using cyclodextrin-nanocellulose composite membrane (10). This indicates that the zinc anode exhibits uniform and dense zinc ion deposition behavior, which is beneficial for the long-term cycling of the zinc anode.

[0057] like Figure 7 As shown, the symmetric battery assembled using a calixarene-nanocellulose composite membrane (20) experienced a short circuit after approximately 2120 h of cycling. The hydroxyl groups of calixarene can undergo esterification or amidation crosslinking with 1,3,5-benzenetriacyl chloride to form a denser composite network, improving the mechanical strength of the membrane. The cavity diameter of calixarene is close to that of zinc hydrate ions, allowing for selective transport of zinc ions through a size sieving effect, effectively improving the desolvation process, reducing interference from other ions, and optimizing the uniformity of zinc deposition.

[0058] like Figure 7 As shown, the symmetric battery assembled using the columnar aromatic hydrocarbon-cellulose nanofiber composite membrane (30) experienced a short circuit after approximately 2240 h of cycling. The columnar cavities of the columnar aromatic hydrocarbons can partially restrict the migration path of zinc ions, effectively improving the desolvation process and avoiding dendrite growth caused by excessively high local current density. In addition, the carboxyl groups form dense hydrogen bonds with the hydroxyl groups of the cellulose nanofibers, significantly improving the mechanical strength of the membrane (such as tensile strength and puncture resistance) and inhibiting zinc dendrite penetration.

[0059] like Figure 7 As shown, the symmetric cell assembled using an acyl chloride nanocellulose membrane (40) experienced a short circuit after 857 h of cycling. The symmetric cell assembled using a nanocellulose membrane (50) experienced a short circuit after approximately 796 h of cycling.

[0060] like Figure 7 As shown, a symmetrical battery assembled using a glass fiber separator (60) experienced a short circuit after 188 hours of cycling. Figure 4 and Figure 6 As shown, after cycling for 60 h using a symmetrical battery assembled with a glass fiber diaphragm (60), a large amount of zinc continuously deposits and forms dendrites, which continue to grow, showing large zinc clusters. After ion beam sputtering, the zinc anode interface exhibits uneven zinc ion deposition behavior, and voids appear inside. This is caused by uneven deposition and dissolution of zinc ions, which is very detrimental to the stable cycling of the zinc anode.

[0061] Experiment Example 3: Electrochemical Reversibility Test of Zinc-Zinc Symmetrical Cells 1. Experimental Procedure The zinc-zinc symmetric batteries assembled in Examples 1, 2, 3, and Comparative Example 3 were subjected to critical current density tests, with current densities starting from 0.5 mAh cm⁻¹.-2 Gradually increase to 10 mAh cm -2 Finally, it returns to 1 mAh cm -2 The test results are as follows Figure 8 As shown.

[0062] The testing equipment used for the electrochemical reversibility test was the Xinwei Battery Testing System.

[0063] 2. Results Analysis Symmetric cells assembled using a glass fiber separator (60) showed improved performance when the current density increased to 10 mA cm⁻¹. -2 It breaks down rapidly. Symmetrical cells assembled using cyclodextrin-nanocellulose composite membranes (10), (11), and (12) can operate normally when the current returns to 1 mA cm⁻¹. -2 Subsequently, the battery voltage hysteresis gradually recovered, indicating that the battery still has a relatively stable voltage distribution under high current conditions and maintains a certain degree of electrochemical reversibility even at large current densities. Furthermore, the results show that with increasing interfacial polymerization time, the voltage of the symmetric battery assembled using the cyclodextrin-nanocellulose composite separator exhibits greater stability under varying current densities.

[0064] Experiment Example 4: Cyclic Performance Test of Zinc-Vanadium Pentoxide Full Cell 1. Experimental Procedure Zinc-vanadium pentoxide full cells assembled using Examples 1, 4, 5, Comparative Examples 1, 2, and 3 were subjected to cycle performance testing at 25 °C with a current density of 3 Ah g. -1 The result is as follows Figure 9 As shown.

[0065] The testing equipment used for the cycle performance testing of the full battery was the Xinwei Battery Testing System.

[0066] 2. Results Analysis The full cell assembled using a cyclodextrin-nanocellulose composite separator (10) had an initial discharge specific capacity of 353 mAhg. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 301 mAh g. -1 The capacity retention rate reaches 85%.

[0067] The full cell assembled using a calixarene-nanocellulose composite separator (20) had an initial discharge specific capacity of 331 mAhg. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 269 mAh g. -1 The capacity retention rate reached 81%.

[0068] The full cell assembled using an aromatic hydrocarbon-nanocellulose composite separator (30) had an initial discharge specific capacity of 312 mAhg. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 270 mAh g. -1 The capacity retention rate reached 86%.

[0069] The full cell assembled using an acyl chloride nanocellulose membrane (40) had an initial discharge specific capacity of 317 mAh g. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 95 mAh g. -1 The capacity retention rate is 30%.

[0070] The full cell assembled using a nanocellulose membrane (50) had an initial discharge specific capacity of 330 mAh g. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 135 mAh g. -1 The capacity retention rate was 41%.

[0071] The full cell assembled using a glass fiber separator (60) has an initial discharge specific capacity of 355 mAh g. -1 After 1500 charge-discharge cycles, the discharge specific capacity is 95 mAh g. -1 The capacity retention rate was 26%.

[0072] As can be seen, the full cells using supramolecular-nanocellulose composite membranes (Examples 1, 4, and 5) all exhibited good capacity retention (>80%), while the unmodified membranes (Comparative Examples 1, 2, and 3) showed lower capacity retention. This is because supramolecular molecules (cyclodextrins, calixarenes, columnar aromatics, etc.) have rigid cavity structures and specific functional groups (such as hydroxyl groups), which can homogenize the zinc ion flow through coordination, reduce local charge accumulation, and thus inhibit dendrite growth. The composite membrane forms uniform micropores through the orderly combination of supramolecular molecules and cellulose, achieving uniform deposition or dissolution of zinc ions.

[0073] In summary, this invention provides a supramolecular-nanocellulose composite separator, its preparation method, and an aqueous zinc-ion battery assembled using the same. The fibrous structure of the nanocellulose membrane is covered by a cross-linked supramolecular polyester layer, resulting in a reduced pore size. Simultaneously, the supramolecular structure and steric hindrance effect effectively regulate the diffusion path of zinc ions, enhancing the desolvation process and controlling zinc ion deposition behavior. Using the supramolecular-nanocellulose composite separator in an aqueous zinc-ion battery can improve the battery's cycle life.

[0074] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A supramolecular-nanocellulose composite membrane, characterized in that, It consists of a nanocellulose membrane and a supramolecular polyester layer on one side of its surface. The supramolecular polyester layer is formed on one side of the nanocellulose membrane by interfacial polymerization using the nanocellulose membrane as a support, supramolecular polymers as reactive monomers, and 1,3,5-benzenetricarboxyl chloride as a crosslinking agent.

2. The supramolecular-nanocellulose composite membrane according to claim 1, characterized in that, The supramolecular material is selected from at least one of cyclodextrin, calixarene, columnar aromatics, and crown ether; the thickness of the nanocellulose membrane is 0.65~0.75 mm.

3. The method for preparing the supramolecular-nanocellulose composite membrane according to claim 1 or 2, characterized in that, The process includes the following steps: fully impregnating the nanocellulose membrane with a supramolecular solution, removing it, and then adding a 1,3,5-benzenetricarboxyl chloride solution to one side of the nanocellulose membrane to induce an interfacial polymerization reaction. After the reaction is complete, the membrane is removed to obtain the supramolecular-nanocellulose composite membrane.

4. The method for preparing the supramolecular-nanocellulose composite membrane according to claim 3, characterized in that, The preparation method of the nanocellulose membrane includes: dissolving cellulose nanofibers in deionized water, stirring thoroughly, and filtering using a vacuum filtration method to obtain the nanocellulose membrane, wherein: The ratio of cellulose nanofibers to deionized water is 0.045~0.06 g:100 mL, preferably 0.06 g:100 mL; The stirring conditions are: rotation speed 500~700 r / min, preferably 600 r / min; stirring time 0.5~2 h, preferably 1 h; The vacuum filtration conditions are as follows: using a filter membrane with a pore size of 40~50 μm and a diameter of 45~60 mm, filtration is carried out for 30~50 min at a temperature of 22~27 ℃ and a vacuum degree of 0.07~0.09 MPa. Preferably, a filter membrane with a pore size of 45 μm and a diameter of 50 mm is used, and filtration is carried out for 40 min at a temperature of 25 ℃ and a vacuum degree of 0.08 MPa.

5. The method for preparing the supramolecular-nanocellulose composite membrane according to claim 3, characterized in that, The solvent of the supramolecular solution is deionized water; the concentration of the supramolecular solution is 0.001~0.1 mol / L, preferably 0.01~0.02 mol / L; the pH value of the supramolecular solution is 10~13; the ratio of the supramolecular solution to the nanocellulose membrane is 6~8 mL: 0.045~0.06 g; The solvent for the 1,3,5-benzenetriformyl chloride solution is n-heptane; the mass ratio of the 1,3,5-benzenetriformyl chloride solution to the solvent in the 1,3,5-benzenetriformyl chloride solution is 1:10~100, preferably 1:40~60, more preferably 1:50; the ratio of the 1,3,5-benzenetriformyl chloride solution to the nanocellulose membrane is 5~6 mL:0.045~0.06 g.

6. The method for preparing the supramolecular-nanocellulose composite membrane according to claim 3, characterized in that, The conditions for the interfacial polymerization reaction are as follows: first react at 23~25 ℃ for 5~40 min, remove excess liquid from the membrane surface, and then react at 50~60 ℃ for 5~40 min; preferably, first react at 23~25 ℃ for 5~20 min, remove excess liquid from the membrane surface, and then react at 50~60 ℃ for 5~20 min.

7. The application of the supramolecular-nanocellulose composite separator according to claim 1 or 2, or the supramolecular-nanocellulose composite separator obtained by the preparation method according to any one of claims 3 to 6, in the preparation of aqueous zinc-ion batteries.

8. An aqueous zinc-ion battery, characterized in that, The supramolecular-nanocellulose composite membrane as described in claim 1 or 2, or the supramolecular-nanocellulose composite membrane obtained by the preparation method described in any one of claims 3 to 6.

9. The aqueous zinc-ion battery according to claim 8, characterized in that, Its type is a zinc-zinc symmetric battery or a zinc-vanadium pentoxide full battery; the separator of the aqueous zinc-ion battery is composed of a glass fiber separator and a supramolecular-nanocellulose composite separator disposed on both sides thereof, wherein the supramolecular-based polyester layer of the supramolecular-nanocellulose composite separator faces away from the glass fiber separator.

10. The aqueous zinc-ion battery according to claim 9, characterized in that, The zinc-zinc symmetric battery includes, in sequence, a negative electrode shell, a spring, a gasket, a zinc negative electrode, a supramolecular-nanocellulose composite membrane, a glass fiber membrane, a supramolecular-nanocellulose composite membrane, a zinc positive electrode, a positive electrode shell, and an electrolyte filled between the zinc negative electrode and the zinc positive electrode, wherein the supramolecular-nanocellulose composite membrane has a supramolecular-based polyester layer located on the side opposite to the glass fiber membrane; The zinc-vanadium pentoxide full cell includes, in sequence, a negative electrode shell, a spring, a gasket, a zinc negative electrode, a supramolecular-nanocellulose composite membrane, a glass fiber membrane, a supramolecular-nanocellulose composite membrane, a vanadium pentoxide positive electrode, a positive electrode shell, and an electrolyte filled between the zinc negative electrode and the vanadium pentoxide positive electrode, wherein the supramolecular-based polyester layer of the supramolecular-nanocellulose composite membrane is located on the side opposite to the glass fiber membrane.